Root system architecture for abiotic stress tolerance in potato: Lessons from plants - Zinta, Rasna; Tiwari, Jagesh Kumar; Buckseth, Tanuja; Thakur, Kanika; Goutam, Umesh; Kumar, Devendra; Challam, Clarissa; Bhatia, Nisha; Poonia, Anuj K.; Naik, Sharmistha; Singh, Rajesh K.; Thakur, Ajay K.; et al. (Frontiers in Plant Science, 2022)
The root is an important plant organ, which uptakes nutrients and water from the soil, and provides anchorage for the plant. Abiotic stresses like heat, drought, nutrients, salinity, and cold are the major problems of potato cultivation. Substantial research advances have been achieved in cereals and model plants on root system architecture (RSA), and so root ideotype (e.g., maize) have been developed for efficient nutrient capture to enhance nutrient use efficiency along with genes regulating root architecture in plants. However, limited work is available on potatoes, with a few illustrations on root morphology in drought and nitrogen stress. The role of root architecture in potatoes has been investigated to some extent under heat, drought, and nitrogen stresses. Hence, this mini-review aims to update knowledge and prospects of strengthening RSA research by applying multi-disciplinary physiological, biochemical, and molecular approaches to abiotic stress tolerance to potatoes with lessons learned from model plants, cereals, and other plants.